TRICARE Applied Behavior Analysis (ABA) Benefit Comparison with Medicaid and Commercial Benefits - Maglione, Margaret A. (RAND Corporation, 2016)
This study compared the Applied Behavior Analysis benefit provided by TRICARE as an early intervention for autism spectrum disorder with similar benefits in Medicaid and commercial health insurance plans. The study focused on comparing a proposed TRICARE reimbursement rate decrease from $125 per hour to $68 per hour for such services performed by a Board Certified Behavior Analyst to reimbursement rates in other plans.